Biofilm colonization in chronic treatment refractory infections presenting with discharging sinuses: A study in a tertiary care hospital of Eastern India - De, Asmita; Raj, Hirak Jyoti; Haldar, Jayeeta; Mukherjee, Poulami; Maiti, Prasanta Kumar (Journal of Laboratory Physicians, 2017)
INTRODUCTION: Treatment refractory chronic recurrent infections mean those chronic infections which recur by same causal agents with similar drug responsiveness after apparent relief following full course of recommended antimicrobial management.MATERIALS AND METHODS: Fifty different samples were collected from patients with chronic surgical site infections, laparoscopic port site infections, anal fistula, mesh hernioplasty, chronic dacryocystitis, chronic osteomyelitis, and chronic burn wounds. Samples were processed for culture, identification, antibiotic sensitivity testing using standard microbiological techniques. Biofilm (BF) forming capacity for aerobic organisms were tested by tissue culture plate method. Those for anaerobes and atypical mycobacteria were studied by a novel method using atomic force microscopy (AFM). In vivo BF colonization in lacrimal mucosae of chronic dacryocystitis, patients were studied from histopathological sections by Gram staining, H and E, and fluorescent in situ hybridization (FISH).RESULTS: Out of fifty different samples, sixty-three isolates were obtained in pure culture as follows: Staphylococcus aureus (25.39%), Escherichia coli (14.28%), Klebsiella pneumonia (14.28%), Mycobacterium abscessus (12.69%), Citrobacter spp. (9.52%), Bacteroides fragilis (6.3%), Pseudomonas aeruginosa (4.7%), Proteus spp. (4.7%), Staphylococcus epidermidis (3.1%), Enterobacter spp. (1.5%), Morganella morganii (1.5%), and Peptostreptococcus spp. (1.5%). Among the isolates, 74% were found to be BF producers in the following frequency: P. aeruginosa 100%, S. epidermidis 100%, B. fragilis 100%, Klebsiella spp. 88.88%, S. aureus 81.25%, M. abscessus 75%, Citrobacter spp. 83.33%, Proteus spp. 66.66%, E. coli spp. 33.33%, and Enterobacter spp. 0%.CONCLUSION: AFM has been proven to be a useful method for detection of in vitro grown BF including those for anaerobes and atypical Mycobacteria. In vivo BF detection becomes possible by FISH. S. aureus was the most common isolate. Among the aerobic isolates, P. aeruginosa and S. epidermidis were found to be the most common BF producers. Atypical mycobacteria were also found to be BF producers. Diagnosis of BF s in chronic infections significantly changes the management strategy as these infections can no longer be dealt simply with antibiotics alone but require mechanical removal of the foci along with antibiotic coverage for complete cure.
Keywords: Atomic force microscopy; biofilm colonization; discharging sinuses